Kesetaraan Gender dalam Pendidikan Islam: Rekonstruksi Hermeneutika Qur’ani Berbasis Maqāṣid Al-Sharī‘Ah dan Sustainable Development Goals (SDGs) - Dewi Indrawati; Windy Dian Sari (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Gender inequality in Islamic education remains a structural issue even though the Qur'an normatively affirms the principle of equality between men and women. This study aims to reconstruct an inclusive Islamic education paradigm through the integration of Qur'anic hermeneutics, maqāṣid al-sharī‘ah, and the Sustainable Development Goals (SDGs). This research uses a qualitative approach of library study type with data sources consisting of classical and contemporary Islamic scholarly treasures, gender studies, as well as recent national and international journal publications. Data analysis is conducted through critical, comparative, and conceptual hermeneutical approaches. The research results show that gender inequality in Islamic educational institutions mainly stems from patriarchal interpretative biases, not from normative Islamic teachings. As a novelty, this study formulates the Gender-Inclusive Islamic Education Model Based on Maqāṣid–Qur'anic Hermeneutics–SDGs as a new conceptual framework for the transformation of Islamic education that is more just, inclusive, and sustainable.